Pharmacotherapeutics of Musculoskeletal Orofacial Pain - Brian E. Cairns; Sujay A. J. Mehta (Journal of the California Dental Association)
Background Musculoskeletal orofacial pain is an umbrella term for pain in the masticatory muscles, temporomandibular joint and their associated tissues. Diagnostic criteria divide these into myalgias, disc displacement, and arthralgias.Types of Studies Reviewed A PubMed search was conducted to identify primary studies, reviews, and meta-analyses that assessed the effectiveness of specific analgesic treatment for “temporomandibular disorders”.Results Few randomized clinical trials of analgesic drugs used to treat musculoskeletal orofacial pain have been undertaken. Current pharmacotherapy for pain management is largely based on clinical experience. It is recommended that analgesic therapy be initiated with a topical non-steroidal inflammatory before moving to oral analgesic or skeletal muscle relaxant therapy.Practical Implications Conservative step-wise analgesic therapy in combination with education and other treatment modalities, such as cognitive behavioral therapy, should be considered in the management of patients with chronic musculoskeletal orofacial pain.Continuing Education Credit Available: A CDA Continuing Education quiz is online for this article: https://www.cdapresents360.com/learn/catalog/view/20The practice worksheet is available online: https://doi.org/10.1080/19424396.2025.2464480